The challenges of building surveyor graduates in Malaysia / Nurul Haziqah Aziz and Nadira Ahzahar - Aziz, Nurul Haziqah; Ahzahar, Nadira (2019)
Building surveying is one of profession that has been established since 1950s. Building surveying is a course that included the study of building maintenance, building design, building construction and study of defects occurred in a building. Although building surveyor profession has been established almost 50 years, but building surveyor is still not well popular among Malaysian. This problem will affect the survival of building surveyor's students and graduates as they must strive and established the profession along with getting a job. Therefore, this paper is to identify the challenges faced by building surveyor graduates. A set of questionnaires were distributed to respondents that graduates from building surveyor course and the data collected was analyzed using SPSS. It was found that awareness and knowledge on BS are still low as they lack information on the profession and professional recognitions. The cause may have resulted in problems on public recognition and poor understanding of the surveyor's skills. Several suggested the profession to have a clear, coherent and relevant identity, with strong professional structures for the profession to survive and gain recognition from the government. Graduates are also recommended to acquire other skills and training for them to be significant to the construction industry.